Opuntia ficus-indica (L.) Mill.: A Multi-Benefit Potential to Be Exploited - Silva, M.A. (2021)
Consumer interest in foods with enhanced nutritional quality has increased in recent years. The nutritional and bioactive characterization of fruits and their byproducts, as well as their use in the formulation of new food products, is advisable, contributing to decrease the global concerns related to food waste and food security. Moreover, the compounds present in these raw materials and the study of their biological properties can promote health and help to prevent some chronic diseases. Opuntia ficus-indica (L.) Mill. (prickly pear) is a plant that grows wild in the arid and semi-arid regions of the world, being a food source for ones and a potential for others, but not properly valued. This paper carries out an exhaustive review of the scientific literature on the nutritional composition and bioactive compounds of prickly pear and its constituents, as well as its main biological activities and applications. It is a good source of dietary fiber, vitamins and bioactive compounds. Many of its natural compounds have interesting biological activities such as anti-inflammatory, hypoglycemic and antimicrobial. The antioxidant power of prickly pear makes it a good candidate as an ingredient of new food products with fascinating properties for health promotion and/or to be used as natural extracts for food, pharmaceutic or cosmetic applications. In addition, it could be a key player in food security in many arid and semi-arid regions of the world, where there are often no more plants.